Composition, diversity and biogeographic affinities of the deep-sea (200–3000 m) fish assemblage in the Great Australian Bight, Australia. (November 2018) - Williams, Alan; Althaus, Franziska; Pogonoski, John; Osterhage, Deborah; Gomon, Martin; Graham, Ken; Appleyard, Sharon A.; Gledhill, Dan; Bray, Dianne; McMillan, Peter; Green, Mark; Doyle, Stephen; et al.
Abstract: The deepest systematic collection of benthic fishes in Australian waters (108 species from 48 families in 200–3000 m depths) was taken by beam trawl during two surveys in the central Great Australian Bight (GAB) in 2015. All samples were on sediment habitats, but some were in close proximity to volcanic seamounts and outcropping rocky seabed in submarine canyons. The great majority of species were previously recorded from Australian waters (90%), and the GAB (75%). A markedly lower proportion of recorded species occurred at greater depths (1700–3000 m) where there had been virtually no previous sampling: 74% in Australian waters, and 30% in GAB waters. The fauna is dominated by families that typify many areas of the global deep sea: rattails (Macrouridae), cut-throat eels (Synaphobranchidae), morid cods (Moridae), oreo dories (Oreosomatidae), slickheads (Alepocephalidae), cusk-eels (Ophidiidae) and halosaurs (Halosauridae). The Macrouridae was most diverse, occurred most frequently, was most abundant (density) in 400 m and all deeper strata, and top ranked by biomass and density in standardised data. The predominant patterns of biogeographical affinities were strongly influenced by depth. Endemic species were most prevalent in shelf break and upper to mid-slope depths (both 52%), and declined with increasing depth (upper to mid-slope species 25%; lower slope/rise 4%), consistent with a general pattern in the Australian ichthyofauna. Fish biomass (gm −2 ) was significantly related to depth, being relatively very low (~0.5 gm −2 ) at 200 m depth, highest at 400 m (~3.4 gm −2 ), then steadily declining with increasing depth to about 0.4 gm −2 at 3000 m depth. Depth was the main factor explaining assemblage structure. There was no clear distinction of assemblages at sites close to structured habitats, and no longitudinal pattern across a gradient of productivity (higher in the east due to summertime upwelling). The GAB is presently being considered for oil and gas exploration in areas extending from the shelf break (200 m) to beyond 4000 m depths. The current data set has the potential to inform biodiversity management in the GAB, including the design of an ecological monitoring program prior to oil and gas exploration, because it includes samples from within and immediately adjacent to the Great Australian Bight Australian Marine Park (GAB AMP) and six active lease blocks. The data set outlined provides a quality assured inventory of fishes, mapping species distributions and associations with habitats in the area of interest, and identifies potential sites of impact and suitable control sites inside and outside marine parks.